Digital transformation of public administration of national security in conditions of hybrid warfare - Dziundziuk , Vyacheslav (Pressing Problems of Public Administration, 2025)
digital transformation, national security, hybrid warfare, public administration, cybersecurity, artificial intelligence, disinformation countermeasures, digital technologies